Tinjauan Yuridis terhadap Penerapan Prinsip Good Corporate Governance (GCG) dalam Undang-Undang No. 40 Tahun 2007 terhadap Praktik Pasar Modal di Indonesia - Mohamad Farhan Wahyudin (Jurnal Hukum, Administrasi Publik dan Negara, 2025)
Good Corporate Governance (GCG) is the main pillar in maintaining investor trust and capital market stability. In the midst of dynamic capital market developments, the principle of transparency and accountability is a key element in building public trust and ensuring investor protection. Law No. 40 of 2007 concerning Limited Liability Companies (UUPT) as the main legal framework for regulating corporate entities in Indonesia, has a strategic position in regulating the implementation of Good Corporate Governance (GGC) principles, especially in the capital market supported by public companies. This study aims to examine the legal implementation of transparency and accountability obligations in Good Corporate Governance (GCG) as regulated in the UUPT and linked to the obligations of public companies in the capital market. This study applies a normative legal approach with a descriptive analysis method to statutory regulations, legal literature, and literature studies from five journals and five relevant law books. The results of this study indicate that the UUPT has emphasized the responsibility of corporate organs in implementing the principles of openness and accountability. Therefore, stricter supervision and strict enforcement of sanctions are needed so that the principles of Good Corporate Governance are truly implemented in real terms.